Assessment of Potential Cytotoxicity During Vital Observation at the BioStation CT - I. S. Trukhan; Т. N Dremina; E. A. Lozovskaya; I. A. Shurygina (Acta Biomedica Scientifica, 2019)
In recent decades, the methods based on the cell technologies have become more relevant for medical and pharmaceutical research. In this paper, weconsidered the BioStation CT using for continuous in vivo observation of Ehrlich ascitic carcinoma cell culture under the influence of two active substances in different concentrations (from 1.25 to 20 mg/l). As a result of the carcinoma cells condition monitoring for 4.5 days it was shown that substance No 2 does not affect the cell viability while substance No 1 causes the carcinoma cell death, and this active substance effect is dose-dependent. Photodocumentation at two-hour intervals allowed us to research differences in the rate of cell destruction (intensive disintegration in the first day with further stabilization of the living cells number or gradual cell death throughout the experiment), as well as differences in the time of 50 % mortality reaching. Thus in the study it was demonstrated that due to the fact that the BioStation CT combines the properties of a CO2 -incubator and a microscope this device is promising for toxicological studies and significantly expands the detection possibilities of processes occurring with living cells for a sufficiently long time period making possible further analysis of the cell behavior characteristics throughout the experiment, and that is fundamentally different from the systems allowing only the final result fixation of long-term active substance exposure.